Insights into greener Miocene biomes and globally enhanced terrestrial productivity from fossil leaves - Tammo Reichgelt; Christopher K. West (Evolving Earth)
Leaf megafloras represent a snapshot of local environmental conditions in Earth's history. As such, they are an important way to understand terrestrial climate analogues for future warmer climate scenarios. Here, we present paleoclimate, productivity, and biome reconstructions of 108 globally distributed Miocene leaf megafloras using a standardized method based on leaf physiognomy. Our results show that the Miocene had higher than modern zonal temperature, precipitation and net primary productivity (NPP) averages, especially for precipitation at latitudes >30°N/°S, suggesting enhanced poleward moisture transport in both hemispheres and a greener biosphere. There is a dearth of Miocene data in the tropics and notably an absence of data points in equatorial localities that have high modern NPP (rainforests), which makes a direct comparison complicated. 89% of investigated sites underwent a precipitation decrease from the Miocene to modern, whereas 66% underwent a temperature decrease, and 60% underwent both a precipitation and a temperature decrease. 67% of sites had more productive biomes during the Miocene than today. Most notably, forested biomes were replaced by more open woodland/shrubland or grassland biomes. Correspondingly, the average NPP decrease from the Miocene to today of our investigated localities was conservatively ∼250 gC m−2 yr−1 or ∼450 gC m−2 yr−1 by comparison of zonal averages. Considered collectively, leaf megafloras reveal an overall greener Miocene world that appears to be largely driven by greater moisture availability.